Sepsis within 30 days following elective surgeries in NSW public hospitals, January 2015-December 2017 - Marashi-Pour, Sadaf; Watson, Diane E (International Journal of Population Data Science, 2020)
Introduction Postsurgical sepsis is a common complication, accounting for one-third of all sepsis cases and associated with higher risk of mortality. Objectives and Approach The Bureau of Health Information (BHI) in New South Wales (NSW), Australia produces independent reports and information about the performance of the healthcare system. Our report investigates the rate of sepsis within 30-days following surgery, and explores variation in risk standardised postoperative sepsis across NSW public hospitals. The study cohort and outcome definitions were drawn from existing international patient safety indicators, modified for appropriate use with Australian linked hospital and mortality data to identify patients transferred, or readmitted to any NSW public or private hospital with postoperative sepsis. Fine and Gray competing risks regression models were used to calculate risk-adjusted rates, and funnel plots were used to identify outliers. Results Rate of 30-day postoperative sepsis was 0.9% among 66,143 adult elective surgeries that met the inclusion criteria during January 2015 to December 2017. Results showed around 33% of post-operative sepsis were identified as occurring during either a transfer or readmission to hospital. Hospital-level unadjusted rates of postsurgical sepsis ranged from 0% to 2% across more than 80 NSW public hospitals. The majority of hospitals (94%) had postoperative sepsis results lower or no different than expected. Conclusion/Implications We explored postoperative sepsis to help understanding of sepsis risk during the follow up period. Results showed a considerable number of postoperative sepsis cases would not have been identified without the use of linked data. Results on hospital risk standardised 30-day postoperative sepsis may prove useful as a screening tool for quality improvement in this area.